Simultaneous Search and Adverse Selection - Auster, Sarah; Gottardi, Piero; Wolthoff, Ronald (Review of Economic Studies, 2025)
Abstract We study the effect of diminishing search frictions in markets with adverse selection by presenting a model in which agents with private information can simultaneously contact multiple trading partners. We highlight a new trade-off: facilitating contacts reduces coordination frictions but also the ability to screen agents’ types. We find that, when agents can contact sufficiently many trading partners, fully separating equilibria obtain only if adverse selection is sufficiently severe. When this condition fails, equilibria feature partial pooling and multiple equilibria co-exist. We show that facilitating contacts can lead to a reduction in welfare. In the limit, as the number of contacts becomes large, some of the equilibria converge to the competitive outcomes of Akerlof, including Pareto-dominated ones; other pooling equilibria continue to feature frictional trade in the limit, where entry is inefficiently high. Our findings provide a basis to assess the effects of recent technological innovations that have made meetings easier.